Global Corporate Debt during Crises : Implications of Switching Borrowing across Markets - Cortina, Juan J.; Didier, Tatiana; Schmukler, Sergio L. (World Bank, Washington, DC, 2020)
This paper studies how crises prompted firms to switch borrowing across markets, impacting the amount borrowed, maturity, and currency denomination at the firm and aggregate levels. Using data on worldwide debt issuance from advanced and emerging economies, the paper shows that firms shifted their issuances between domestic and international syndicated loans and corporate bonds during financial crises. Firms reduced their borrowing in shock-hit markets but increased it in other debt markets. Firms also moved toward longer-term markets, maintaining (or even increasing) their borrowing maturity. As they moved toward domestic markets during international crises, firms reduced the share of foreign currency debt. The opposite occurred during domestic crises. Large firms were the ones that switched between international and domestic markets, affecting aggregate capital raising activity. The analysis of four distinct markets generates patterns consistent with credit supply shocks that are different from those obtained when studying the dynamics of individual markets.